On empowerment and disempowerment of parents - Van der Wolf, Kees (International Journal about Parents in Education, 2023)
More and more aspects of everyday life are placed under the control of specialists, because we have become convinced that a professional approach to problems is better than that of a layman. Many parents think so too. They think dealing with children in this complex society is a tough job: they are glad if others are prepared to think along and join in, so that the responsibility for the upbringing can be shared. They are quite pleased to have specialists support them in parenting.